Determinantes e eficácia da lealdade partidária no Brasil: uma análise das estratégias dos candidatos a prefeito e vereador - Pereira, Leila Albuquerque Rocha (2015)
Brazil’s current political system is marked by the large number of parties and also by strong inter-party transit: today, more than 30 parties dispute elections and in both the legislative and the executive positions, the number of politicians with exclusive membership to a single party has fallen considerably. In this scenario, the investigation of the characteristics of the party switching process is fundamental for a better understanding of the Brazilian political party system. Seeking to deepen the knowledge on this topic, we set out to answer two questions: 1. Is the mayors and the city-councilman decision concerning party switching affected by their performance in the elections and also by the result of the elections to the state government? 2. Are the strategies of party switching or party loyalty effective? To answer these questions, we used data from municipal elections for mayor and city-councilman from 2000 to 2012 and estimated the above effects through Discontinuous Regression Design and also using the Instrumental Variables Method.